The "Eyewitnesses" of Jesus and their teaching : a historical-analytical study - Younes, Marwan Hamdy (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
Jesus is one of the great historical figures who was able to change the course of history. Despite his greatness as a historical figure, the controversy regarding his message and teachings is substantial. This controversy is not only confined to the major monotheistic revealed religions, but was likewise prevalent between Christian communities over history, as in the present time. This research attempts to examine the essence of the Message of Jesus from a purely historical perspective, disregarding any theological pre-assumptions. The research focuses on: firstly, the socio-political and religious setting during the ministry of Jesus; secondly, the significance of his disciples' accounts as his “Eyewitnesses,” as opposed to those that believed in him but did not see him; and lastly, the conflict between his disciples and Paul of Tarsus, who is the main contributor of the New Testament's theology. This research has reached the following findings: firstly, the Roman Empire's control and influence of the socio-political and religious context in Palestine and the Mediterranean was not only confined to the period of their political dominance, but was prevalent thereafter upon the authors of the New Testament when it was first written after the first Jewish-Roman war. Secondly, the depicted image of the disciples of Jesus in the New Testament has no real historical basis, for they were pious Jewish men and women, not Gentiles. Thirdly, the Roman Empire was in a clear conflict with the community that John and Jesus have formed. Fourthly, the Apostle Paul of Tarsus was always loyal to his Roman citizenship throughout his life, even if he claimed to follow Jesus; for his teachings did not support it. Lastly, Paul of Tarsus is the main contributor to the theology of the present-day Christianity. This thesis gives ample evidence that most of the theology of Paul in the New Testament has no historical basis that goes back to its first founder, Jesus. Instead, it is taken from Hellenic and Roman belief systems, and over time, came to be regarded as the core message of Jesus.